2018
DOI: 10.1002/btpr.2684
|View full text |Cite
|
Sign up to set email alerts
|

Sequencing and phylogenetic analyses of talaromyces amestolkiae from amazon: A producer of natural colorants

Abstract: The population interest in health products is increasing day-by-day. Thus, the demand for natural products to be added in food and pharmaceutical commodity is also rising. Among these additives, colorants, which provides color to products, can be produced by microorganism through bioprocess. Looking for new source of natural colorants, fungi have been employed to this purpose producing novel and safer natural colorants. So, the main goal of this study was to describe a Talaromyces species able to produce natur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(4 citation statements)
references
References 60 publications
0
3
1
Order By: Relevance
“…Studies have reported that organic nitrogen sources are better than inorganic ones to promote pigment production by Talaromyces/Penicillium [32]. However, in this study, signi cant changes were not observed in the pigment production and colour characteristics when supplemented with organic and inorganic nitrogen (Table 2).…”
Section: Combined Effect Of Carbon and Nitrogencontrasting
confidence: 68%
See 1 more Smart Citation
“…Studies have reported that organic nitrogen sources are better than inorganic ones to promote pigment production by Talaromyces/Penicillium [32]. However, in this study, signi cant changes were not observed in the pigment production and colour characteristics when supplemented with organic and inorganic nitrogen (Table 2).…”
Section: Combined Effect Of Carbon and Nitrogencontrasting
confidence: 68%
“…Similarly, the highest redness a value was found in basal medium supplemented with 1% xylose (49.55 ± 1.62), whereas the least was in sucrose (5.30 ± 1.13). The production of pigments by T. amestolkiae DPUA 1275 was explained utilizing glucose as carbon source and careful selection of nitrogen source [32]. Carbon source addition (glucose, fructose, sucrose, xylose, maltose, and lactose) to the WBH basal medium produced a signi cant increase in both pigment and biomass yield (Table 1).…”
Section: Supplementation Of Carbon Source To Wbhmentioning
confidence: 99%
“…In the same way, other authors [ 49 , 50 ] have reported species of Penicillium and Talaromyces with maximum absorption wavelengths in the UV region, although yellow and orange pigments are usually exhibited at 410 and 470 nm, respectively [ 51 ]. Accordingly, Talaromyces albobiverticillius , Talaromyces amestolkiae , and T. purpureogenus have been reported to produce yellow-orange pigments in the visible region, although these species are also able to produce a red pigment [ 37 , 51 , 52 , 53 , 54 , 55 ]. Commonly, chromophores of polyketide-based pigments, such as azaphilones and anthraquinones, absorb in the UV region (200–300 nm), whereas the nature and the number of substituted functional groups determines absorbance in the visible region (400–700 nm) [ 37 ].…”
Section: Resultsmentioning
confidence: 99%
“…Even so, filamentous fungi are the most suited microorganism producers of xylanase due to their capacity to generate large amounts of extracellular enzymes using a wide range of low-cost substrates, such as waste and byproducts. Among the filamentous fungi, Aspergillus, Trichoderma, and Talaromyces genera, which include the Talaromyces amestolkiae (previously called Penicillium purpurogenum) are described in the literature as enzyme producers [13][14][15].…”
Section: Introductionmentioning
confidence: 99%